Microgravity Removes Reaction Limits from Nonpolar Nanoparticle Agglomeration. Issue 46 (10th October 2022) - Pyttlik, Andrea; Kuttich, Björn; Kraus, Tobias
Abstract: Gravity can affect the agglomeration of nanoparticles by changing convection and sedimentation. The temperature‐induced agglomeration of hexadecanethiol‐capped gold nanoparticles in microgravity (µ g) is studied at the ZARM (Center of Applied Space Technology and Microgravity) drop tower and compared to their agglomeration on the ground (1 g). Nonpolar nanoparticles with a hydrodynamic diameter of 13 nm are dispersed in tetradecane, rapidly cooled from 70 to 10 °C to induce agglomeration, and observed by dynamic light scattering at a time resolution of 1 s. The mean hydrodynamic diameters of the agglomerates formed after 8 s in microgravity are 3 times (for low initial concentrations) to 5 times (at high initial concentrations) larger than on the ground. The observations are consistent with an agglomeration process that is closer to the reaction limit on thground and closer to the diffusion limit in microgravity. Abstract : The rate of temperature‐induced agglomeration of nonpolar gold nanoparticles in normal gravity differs from that in microgravity. The authors use dynamic light scattering to follow the growth of agglomerates in dispersion on the ground and in a drop tower. The differences in growth rates indicate a transition from a more reaction‐limited process on the ground to a more diffusion‐limited agglomeration in microgravity.